Pola kepadatan populasi vektor penyakit DBD di permukiman penduduk bantaran Sungai Martapura Kecamatan Martapura Timur Tahun 2017 - Yohanes Joko Supriyadi; Darmiah Darmiah; Yuniarti Suryatinah (Balai Litbangkes Tanah Bumbu, 2018)
Martapura river water is one of the source of water used for daily use by residents who live along the banks of the river Martapura. Almost every house along the river Martapura does not have adequate clean water facilities and is highly dependent on river water. The objective of the study was to know the pattern of population density of dengue fever vector in residential area of ​​river Martapura. This type of analytic research, using a cross sectional design. The population of all Aedes sp mosquitoes and all residents in the residential area of ​​river Martapura. The sample is partially Aedes sp mosquitoes and residents in the residential area of ​​the river Martapura river, the village Antasan Senor, Antasan Senor Ilir, and the village of Mekar). Purposive Sampling Sampling Technique. Methods of gathering observations, interviews and identification. Analytical data processing and analysis with one way ANOVA test. The results showed that the population density vector category